Accessibility and Disability-Inclusive Urban Planning in Kathmandu Metropolitan City - Singh, Ramesh Prasad; Dhakal, Januka (International Research Journal of MMC, 2024)
This research aims to explore the importance of accessibility and disability-inclusive urban planning. For this, it analyzes the problems of disabled people, especially physically disabled people, living in Kathmandu Metropolitan City. The review of the literature shows that people with disabilities face a widespread lack of accessibility to build environments, from roads and housing to public buildings and spaces and basic urban services such as sanitation and water, health, education, transportation, and emergency response and resilience programs. Particularly, one of the main problems in Kathmandu Metropolitan City is the inaccessibility of urban public spaces such as sidewalks, bus stops, pedestrian crossings, etc. for people with all kinds of abilities. Persons with disability (PWDs), often struggle with the complexities of the built environment in urban areas that hinder their equal participation in daily activities. So, there is a need for accessibility and disability-inclusive urban planning in Kathmandu metropolitan city.